Potency of Seaweeds Specieses as Minerals Supplement for Dairy Cattle - Agustin - Herliatika (Buletin Ilmu Makanan Ternak, 2017)
Indonesia is a maritime country, rich in biodiversity such as seaweeds which have potential as animal feedstuffs. Previous study showed that the seaweeds high in ash contents and have potential as mineral sources for dairy cattle. This study was aimed to compare several seaweeds species’s (Sargassum sp., Gelidium sp., Gracilaria sp., Eucheuma cottonii and giant Eucheuma cottonii) potential as mineral sources for dairy cattle. Parameters observed in this study were macro mineral contents (Ca, P, Na, Cl, Mg, S), the mineral solubility in HCl and rumen liquor, and estimate of their availability in rumen and abomasum. This study used completely randomized design except for solubility in rumen liquor study which was used completely blocked design. The collected data were analysed using ANOVA followed by Duncan multiple rank test except for mineral contents which used descriptive statistics. The results showed that all seaweed tested high in macro mineral contents except for Gelidium sp. Their solubility in HCl and rumen liquor were also high. It is concluded that all seaweed tested were good mineral sources for dairy cattle, except for Gelidium sp.